University Libraries in Research and Innovation: An Analytical Review - Mr. Jagtar Singh; Dr. Manjeet Kaur (Journal of International Islamic Law, Human Right and Public Policy, 2026)
A paradigm shift is taking place in which the role of libraries at universities is changing towards being more than mere guardians of information and becomes more of a participant in the research and innovation process. In a digital scholarly age, with data heavy research and open science, libraries are crucial in underpinning the entire research pathway and developing an ecosystem of innovation in universities. This paper contains a more thorough review and study of the changing role of university libraries in the supporting research and innovation process. The study is based on a rich amount of global literature, policy frameworks, and best practices and explores the role of the library in contributing to research productivity, scholarly communication, research data management, interdisciplinary collaboration, and knowledge dissemination of innovation. The paper also recognises structural, financial, and professional issues that affect university libraries and gives future plans of how they can enhance their place in institutional research and innovation agenda. The review states that the re-branding of university libraries as active research and innovation partners is the key to improving the quality of academics, international presence, and influence on society.